Internationalising higher education in Cambodia, Lao PDR, Myanmar, and Viet Nam: challenges and approaches - Hill, Christopher; Hell, Stefan; Van Cauter, Kevin (Studies in higher education (Dorchester-on-Thames), 2021)
With increasing focus placed on global rankings, partnerships, and student mobility, institutions are increasingly embedding internationalisation within their strategic language and approach. This paper examines the four countries of Cambodia, Lao PDR, Myanmar, and Viet Nam (CLMV) to explore the challenges and opportunities for institutions in this regard. The subject is of value as developing nations are often operating on an imbalanced playing field. The researchers adopted a qualitative mixed method of surveys and interviews to identify, quantify, and discuss the key challenges and drivers for internationalisation. Respondents from 17 institutions took part in the process and the findings are presented in terms of a series of recommendations. This research was conducted in collaboration with EU-ASEAN SHARE and British Council.